Strategi Penciptaan Iklim Kelas Kondusif melalui Pengelolaan Kelas dan Penguatan Etos Kerja Guru dalam Meningkatkan Kinerja Pembelajaran - Duwi Sakiatul Rohmaniah; Karlinda Anna Mudrikah; M. Haikal Ardani; Moh. Iqbal Maulana; Yunda Nurul Millati Hoiriyah; Mu’alimin Mu’alimin (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze strategies for creating a conducive classroom climate through the integration of classroom management and strengthening teachers' work ethic. The research employs a qualitative literature review method, collecting and analyzing various relevant sources. Findings indicate that a conducive classroom climate is influenced by three main factors: (1) effective classroom management, including physical environment arrangement, implementation of democratic approaches, and participatory learning methods; (2) teachers' work ethic encompassing commitment, creativity, and the ability to build positive interactions; and (3) institutional support through facilities and teacher development programs. Challenges such as administrative burdens and lack of teacher appreciation are also discussed. The study concludes that holistic integration of classroom management and teacher work ethic enhancement can create an optimal learning environment. Recommendations include improving teacher training, providing supporting facilities, and conducting further research to test this model's effectiveness in various contexts.